The Impact of E-Marketing on the Preference to Purchase Hybrid Cars by Increasing Awareness: An Empirical Study of Hybrid Car Users in the Northern Border Region, Saudi Arabia - Arous, Jamal Ali; Louail, Bilal; El Rabbat, Samar Ahmed; Hima, Nadya Ali; Barakat, Shaima Ahmad (Engineering, Technology & Applied Science Research, 2024)
This research examines the impact of e-marketing on consumers’ preference to purchase hybrid cars, through the conduction of a field study on the hybrid car users in the Northern Border Region in Saudi Arabia. The research aims to comprehend the relationship between e-marketing campaigns and increasing consumer awareness of the benefits of hybrid cars, and how their decisions are affected by this awareness when purchasing cars. The research aims to shed light on the role of e-marketing in encouraging the use of hybrid cars and identifying the factors influencing consumers’ decisions in this context. The research aims to identify factors influencing users’ responses to such information, including advertising campaigns, environmental attitudes, future orientations, and governmental incentives. A survey was conducted to a total of 385 hybrid car users and data analysis relied on structural equation modeling deploying the Amos software. The results indicate the existence of a relationship and impact between e-marketing campaigns and user awareness, leading to an increased preference for hybrid cars.